2022
DOI: 10.31083/j.jin2101036
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological performance after carotid endarterectomy

Abstract: Background: Internal carotid endarterectomy (CEA) is a method of stroke prevention in patients with severe internal carotid artery (ICA) stenosis. Patients with significant carotid stenosis tend to have lower cognitive performance than those without significant stenosis. This is believed to be due to hypoperfusion or ongoing microembolization to the brain. Methods: We evaluated 60 patients with at least 70% ICA stenosis with the RBANS test (Repeatable Battery for the Assessment of Neuropsychological Status, Cz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…One explanation for the less-thanexpected IPH(1) group's performance is microembolization during the intervention. 41 An association between vulnerable plaque and postintervention ischemic events has been previously shown. [42][43][44][45] During carotid endarterectomy, IPH increased the embolization risk, specifically during the dissection phase.…”
Section: Discussionmentioning
confidence: 88%
“…One explanation for the less-thanexpected IPH(1) group's performance is microembolization during the intervention. 41 An association between vulnerable plaque and postintervention ischemic events has been previously shown. [42][43][44][45] During carotid endarterectomy, IPH increased the embolization risk, specifically during the dissection phase.…”
Section: Discussionmentioning
confidence: 88%
“… 7 reported that the MMSE results were often normal in patients with right-sided hemispheric stroke or mass lesions, whereas Kramska et al. 18 used the Repeatable Battery for the Assessment of Neuropsychological Status to minimize the potential learning effect responsible for higher postoperative scores when other tests are used. This shows the need for more unified and adaptable tests and the use of common standards, per the Hachinski et al.…”
Section: Discussionmentioning
confidence: 99%
“…Watanabe et al 16,17 noted the differences in the results obtained using the Montreal Cognitive Assessment (MoCA) and Mini-Mental State Examination (MMSE) and the superiority of the MoCA in detecting mild cognitive impairment. Moreover, Johnston et al 7 reported that the MMSE results were often normal in patients with right-sided hemispheric stroke or mass lesions, whereas Kramska et al 18 used the Repeatable Battery for the Assessment of Neuropsychological Status to minimize the potential learning effect responsible for higher postoperative scores when other tests are used. This shows the need for more unified and adaptable tests and the use of common standards, per the Hachinski et al recommendations.…”
Section: Discussionmentioning
confidence: 99%